Strategi Pemberdayaan Ekonomi Jemaat Sebagai Aksi Pastoral - Mangintiu, Meylan; Nyortetma, Devence; Salindeho, Sri Apria; Bambung, Charolin; Papehasen, Christian; Amping, Eunike; Inaku, Rahel; Manggiwu, Sindy; Biala, Trisakti; Binilang, Yanly; Hender, Solistiyo; Piandatu, Natasya (HOSPITALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
By exploring various plans that are prepared as an integral part of the church's pastoral action, through approaches that can improve the economic welfare of the congregation and practical spiritual support from the church. In several sections it can be seen how the church plays an active role in encouraging economic independence which strengthens community life and improves the quality of life of the congregation, and we need to know that the factor that drives congregational independence is the pastoral role in the community service program that has been implemented, so it is necessary for us to understand how step by step the pastoral service strategy is implemented at GMIST Wori Congregation in the "Community Service" (PKM) activity. In general, pastoral care is a fundamental aspect of church life that involves spiritual, emotional and social support for the congregation. A pastoral approach focuses on deep interpersonal relationships, supporting individuals in facing life's challenges, and helping them find meaning and purpose in the context of the Christian faith. What is discussed in the pastoral care program is so interesting, that there are ideas that are formulated related to teaching about economic empowerment, which are often forgotten and rarely discussed, so that this becomes a small part of what causes divisions within the congregation without realizing it. So we will examine how pastoral service can be used to empower the congregation's economy, with the title "Congregation Economic Empowerment Strategy as Church Pastoral Action".